ESR1 Regulates the Obesity- and Metabolism-Differential Gene MMAA to Inhibit the Occurrence and Development of Hepatocellular Carcinoma - Zhang, Yiyin; Cheng, Jiaxi; Zhong, Cheng; Xia, Qiming; Li, Yirun; Chen, Peng; Fan, Xiaoxiao; Mao, Qijiang; Lin, Hui; Hong, Defei (Frontiers in Oncology, 2022)
Obesity is often regarded as a factor that promotes tumorigenesis, but the role of obesity in promoting hepatocellular carcinoma (HCC) is still controversial. We compared the trend change of 14 obesity-related genes in the formation and development of HCC in normal, adjacent and HCC tissues. Mendelian randomization (MR) analysis was used to verify the relationship between obesity and HCC occurrence. MMAA was discovered as an obesity and metabolism-differential gene, and its function in HCC was tested in vitro and in vivo. Finally, we explored how obese female patients with originally high expression of female estrogen receptor (ESR1) directly upregulated MMAA to interfere with the progression of HCC. Fourteen obesity-related genes were downregulated in adjacent and tumoral tissues compared with normal liver tissues, which indicated that obesity may be inversely related to the occurrence of HCC and was consistent with the results of MR analysis. We also discovered that MMAA is a metabolic gene closely related to the occurrence and development of HCC by mining the TCGA database, and it functioned as an anti-tumor-promoting role in HCC by damaging mitochondrial function and preserving the redox balance. We further verified that obese females with high expression of ESR1 can regulate MMAA to protect HCC from progression. This study elucidates that obesity might be a protective factor for female HCC patients, as they originally highly expressed ESR1, which could upregulate MMAA to suppress tumor growth and participate in metabolic reprogramming.